A Process Model for the GIS Software Evaluation and Selection - Amir, Amiza (2006)
Geographic Information System (GIS) is an example of a commercial-off-the-shelf (COTS) based system to solve the needs of spatial storage and is used widely in various applications. More and more GIS software were developed to solve the requirement of the GIS application environment that becoming more sophisticated and dynamic. While some of them are generic and can be used in various applications, others are more confined or more specific. GIS is a decision support system. Therefore, unlike other systems such as management information system (MIS) whose major impacts are on efficiency. GISs effect user effectiveness in their decision making process. The GIS software packages have their particular strengths and weaknesses, thus making the selection and purchase of a GIS software package difficult. Buying the appropriate GIS software package is important and can help cut down on costs. This thesis aims to suggest an alternative method to GIS software evaluation and selection process and assure the quality of the GIS software. This thesis involves the development of a process model as alternative method to GIS software evaluation and selection process. The process model is developed based on OTSO method and uses the Analytic Hierarchy Process as a decision making technique. This research includes the development of a prototype, which is called the GIS CHOICE. The GIS CHOICE is a computer-based environment that supports the model. GIS CHOICE can improve the existing GIs software evaluation and selection process. This process model and tool provide a flexible and systematic solution for each GIS software selection and assure the effectiveness of GIS application in the organization’s work system.